Degradation of epoxidized natural rubber compatibilized linear low density polyethylene/soya powder blends: The effect of natural weathering - Sam, Sung Ting, Dr. (Walter de Gruyter GmbH, 2014)
Link to publisher's homepage at http://www.degruyter.com/